Implementation of Economic Altruism Education in Character Formation of Graduate Profile Dimensions - Yunita Adiningsih; Suranto Suranto (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This study examines the application of economic altruism education in shaping student character according to the Graduate Profile dimensions at SMK Muhammadiyah 2 Karanganyar. Altruism is positioned as a moral foundation that aligns with the culture of mutual cooperation and the principles of economic justice that have developed in the Indonesian social context. This study used a qualitative approach with a case study design, involving teachers and students in the marketing subject. Data were obtained through learning observations, in-depth interviews, and documentation analysis, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The results of the study indicate that altruistic values are systematically integrated into all stages of learning, from planning and developing teaching modules to implementing learning and assessment. Teachers incorporate elements of cooperation and social awareness into learning outcomes and facilitate collaborative activities, particularly through retail business practice assignments that require teamwork and shared responsibility. In the learning process, teachers act as facilitators who observe the dynamics of student interactions, reinforce prosocial attitudes, and implement authentic assessments that encompass cognitive, affective, and social aspects. Overall, the application of economic altruism values has been shown to support the strengthening of the Pancasila Student Profile dimensions, particularly mutual cooperation, noble character, and independence. These findings confirm that economic altruism education not only contributes to improving academic competence but also plays a crucial role in shaping students' social character.